Zooplankton functional traits as a tool to assess latitudinal variation in the northern-southern temperate European regions during spring and autumn seasons. (October 2020) - Kuczyńska-Kippen, Natalia; Špoljar, Maria; Zhang, Chen; Pronin, Małgorzata
Highlights: Abiotic variation existed between water bodies in Croatia and Poland. Neither ecological nor feeding groups responded to regional specificity. Ecological and feeding traits were determined by morphometric and trophic properties. Taxonomic approach (dominating species) indicated regional distinctiveness. Abstract: Zooplankton structure may serve as predictor of a multiplicity of environmental conditions, including long-scale distance between shallow water bodies. Two different categories of zooplankton indices (1/ biocoenotic indices, including dominating species; 2/ trait-based approaches, including ecological groups: littoral vs . pelagic community and functional feeding groups) were compared in small water bodies of two regions of Europe (1/ Northern water bodies (N-WB): Poland, and 2/ Southern water bodies (S-WB): Croatia). We hypothesized that latitudinal variation between these regions will result in distinguishing specific environmental factors that in turn affect the structure of zooplankton communities. In order to avoid weather extremes in both countries, we focused our research on less frequently investigated periods of the year; during the unvegetated and mild-temperature seasons (spring and autumn). Despite well pronounced differences in some abiotic characteristics of water between both regions (higher chlorophyll a and phosphorus contents in N-WB compared to better oxygenated waters and higher water transparency in S-WB) we observed rather uniform pattern with respect to zooplankton trait-based indices in N-WB and S-WB. This may have been caused by poor habitat heterogeneity due to macrophyte absence (spring) or decaying state (autumn) and poor food supply during the spring/autumn seasons. Planktonic and detrivorous rotifers (e.g. from genera Keratella and Brachionus ) predominated in both countries. Ecological and trophic functional traits were mostly determined by the morphometric and trophic properties. Irrespective of latitudinal variation, water transparency emerged as a significant factor, negatively affecting zooplankton abundance, especially the dominating detrivorous rotifers, and positively littoral zooplankton. Moreover, an increase in water area, related to higher contents of nutrients and food resources, supported a higher abundance of the majority of zooplankton feeding guilds. Our results suggested that only at the level of taxa the distinctiveness between the two European regions, northern and southern, was clear. Apart from taxa dominating in both countries ( Keratella cochlearis, Bosmina longirostris ), Polyarthra spp. and Eudiaptomus gracilis dominated exclusively in Croatia and Cyclops sp. in Poland during the unvegetated and temperature-transitional seasons. This indicates that only the taxonomic approach, referring to certain dominating species, was a sensitive tool. Functional trait-based approaches, despite providing relevant information on the quality of aquatic ecosystems, are not sufficiently sensitive in identification of latitudinal variation of zooplankton in the spring/autumn season.